Nitric therapy in preterm infants: rationalised approach based on functional neonatal echocardiography. (11th December 2015) - Cheng, Daryl R.; Peart, Stacey; Tan, Kenneth; Sehgal, Arvind
Abstract: Aim: Use of inhaled nitric oxide (iNO) in preterm infants is not supported by current evidence. In 2013, in Australia and New Zealand, 14% infants' ≤25 weeks of gestations were administered iNO. Within the cohort administered iNO, we aimed to identify subgroups where it may be more efficacious and compared characteristics before and after the set‐up of the functional echocardiography (fEcho) programme. Methods: A retrospective audit for the period 2000–2013 involving preterm infants administered iNO in the first four weeks of life was performed. Comparisons were made between the two time epochs: up to 2007 and post‐2007. Results: Eighty‐five infants fulfilled the inclusion criteria; 62 (73%) were ≤28 weeks of gestation; 51 (60%) survived. Amongst survivors, gestation and birthweight were higher and oxygenation index (OI) was lower. Fourteen (16.5%) infants weighed small for gestation age; survival was lower in this subgroup (6/14, 43%, p = 0.0005). The fEcho programme increased prenitric assessments for a definitive diagnosis and monitoring; iNO was started earlier, at a lower OI with a trend towards reduced usage (hours). Conclusion: Characteristics of subgroups (within the cohort of infants ≤34 weeks of gestation) more likely to benefit from iNO therapy were identified. Use of fEcho could rationalise usage. Abstract :